Digitised Newspapers – A New Eldorado for Historians? - Bunout, Estelle; Ehrmann, Maud; Clavert, Frédéric (2022)
Digitization technologies applied to historical newspapers have changed the research landscape historians were used to. An Eldorado? Despite unquestionable merits, the new digital affordance of historical newspapers also brings drawbacks and possible pitfalls which need to be carefully assessed.